Sustainable logistics: an emerging research area - Mohan Kumar, Kavigtha; Abd Rahman, Azmawani; Sambasivan, Murali (IEEE, 2015)
Logistics industry in Malaysia is rather treated as strategic industry for economic growth and one of the key industries for Third Industrial Master Plan (IMP3) in Malaysia. It is worthwhile to study the environmental sustainable logistics practices of logistics service providers and its effect on their logistics performance, particularly in road freight transportation industry. The study proposed a conceptual framework for sustainable environmental logistics practices on logistics performance, which may be customized for other industries as well.